Kerjasama China Dengan Pakistan Dalam Wadah Koridor Ekonomi China-Pakistan (CPEC) Tahun 2015 - Muhammad Luthfi Ikhwan (HI 16 UMY 182, 2016)
*182 This article will discuss about the reason of Chinese interests and make pakistan as a partner in china's economic corridors of pakistan (CPEC) by 2015. The Economic Corridor dinisiasi cooperation by china utilized by China to realize its importance. The interests sought to be realized China when making Pakistan as a partner. There are a number of interests that would be obtained by China when it chose Pakistan as a partner. But as we know together, Pakistan is not among the countries that are considered developed countries, particularly in the area of South Asia.